Domestic and Commercial Vegetable Gardening in Dawson City, Yukon Territory, 1980 - McCracken, Colleen; Revel, Richard D. (ARCTIC, 1982)
Canadian subarctic agriculture has not been a widespread practice. Because of increasing northern populations associated with industrial development, and the high cost of fresh produce, the practicality and success of subarctic gardening are examined. Dawson City was chosen for study because of its long history of gardening. In 1980 there were 50 domestic gardens, 56 greenhouses, and three commercial gardens which supplied produce both locally and to Whitehorse and Inuvik. The study documents the following crops: cabbage, cauliflower, broccoli, Brussels sprouts, carrots, turnips, kohlrabi, radish, beans, peas, potatoes, lettuce, kale, beetroot, Swiss chard, celery, onions, cucumber, tomatoes, zucchini, corn, peppers, leeks, squash, sunflowers and a large variety of herbs. The specific crop varieties used by gardeners are noted along with observations on their relative success, planting and harvesting dates and special gardening practices.Key words: agriculture, gardening, vegetable cultivation Mots clés: agriculture, jardinage, culture de légumes